Enhanced cellular uptake and long-term retention of chitosan-modified iron-oxide nanoparticles for MRI-based cell tracking - Bakhru SH (Dove Medical Press, 2012)
Sasha H Bakhru,1 Eda Altiok,2 Christopher Highley,1 Daniel Delubac,1 Joseph Suhan,2 T Kevin Hitchens,2 Chien Ho,2 Stefan Zappe11Department of Biomedical Engineering, 2Department of Biological Sciences, Carnegie Mellon University, Pittsburgh, PA, USAAbstract: Tracking cells after therapeutic transplantation is imperative for evaluation of implanted cell fate and function. In this study, ultrasmall superparamagnetic iron oxide nanoparticles (USPIO NPs) were surface functionalized with water-soluble chitosan, a cationic polysaccharide that mediates enhanced endocytic uptake, endosomal escape into the cytosol, and subsequent long-term retention of nanoparticles. NP surface and chitosan were independently fluorescently labeled. Our NPs enable NP trafficking studies and determination of fate beyond uptake by fluorescence microscopy as well as tracking of labeled cells as localized regions of hypointensity in T2*-weighted magnetic resonance imaging (MRI) images. Adult rat neural stem cells (NSCs) were labeled with NPs, and assessment of NSC proliferation rates and differentiation potential revealed no significant differences between labeled and unlabeled NSCs. Significantly enhanced uptake of chitosan NPs in comparison to native NPs was confirmed by transmission electron microscopy, nuclear magnetic resonance (NMR) spectroscopy and in vitro cellular MRI at 11.7 Tesla. While only negligible fractions of native NPs enter cells, chitosan NPs appear within membranous vesicles within 2 hours of exposure. Additionally, chitosan-functionalized NPs escaped from membrane-bound vesicles within days, circumventing NP endo-lysosomal trafficking and exocytosis and hence enabling long-term tracking of labeled cells. Finally, our labeling strategy does not contain any NSC-specific reagents. To demonstrate general applicability across a variety of primary and immortalized cell types, embryonic mouse NSCs, mouse embryonic stem cells, HEK 293 kidney cells, and HeLa cervical cancer cells were additionally exposed to chitosan-USPIO NPs and exhibited similarly efficient loading as verified by NMR relaxometry. Our efficient and versatile labeling technology can support cell tracking with close to single cell resolution by MRI in vitro, for example, in complex tissue models not optically accessible by confocal or multi-photon fluorescence microscopy, and potentially in vivo, for example, in animal models of human disease or injury.Keywords: nanoparticle, iron oxide, chitosan, neural stem cell, cell tracking